A Glimpse at the Future: Exploring the Prospects of Processing Instruction and Implicational Universals for TEFLIN - Patrisius Istiarto Djiwandono (TEFLIN, 2003)
This paper highlights two of the implications of language acquisition research, namely, Processing Instruction, and Implicational Universals, and explores their potentials for English language teaching in the 21st century. Through the discussion on these two ideas, it is expected that the paper can serve to prod language educators and teaching practitioners to find a clearer direction for their step forward.